(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
A series of 3-ethyl-2,6-diarylpiperidin-4-one thiosemicarbazone and 3,5-dimethyl-2,6-diarylpiperidin-4-one thiosemicarbazone were synthesised. The thiosemicarbazones were subjected to cyclic voltammetric study using graphite electrode with variable scan rate at moderate acidic conditions maintained in the electrolytic solution. The reduction takes place by two electron transfer and the reaction is pH dependent. The reduced products were isolated and purified by column chromatography. The structure was proved by 1H and 13C NMR spectroscopy. The electrode process was found to be irreversible and diffusion controlled. Further the products were analysed for anti fungal activity in which nitro substituted compound showed high inhibition towards the fungi Asperillus niger